Multiple Ionization of Ne in coincidence with partially stripped B 2+ ions in the intermediate energy regime - Wolff, W. (2012)
A projectile ion-recoil ion and electron-recoil ion coincidence technique has been used to study the multiple ionization process in collisions of 0.75-4.0MeV B2+ with Ne atoms. Absolute total and partial pure ionization cross sections are reported for the first time at these impact energies with the present setup. The relative contribution of each recoil charge state has been investigated. The experimental data are compared to CDW-EIS calculation and with He2+ projectiles. The data throw further light on the effect of projectile screening in the ionization of multi-electronic targets and provide a support for the validity of the CDW-EIS model in this intermediate-to low velocity regime.